Creep Behavior of Graphene Oxide, Silk Fibroin, and Cellulose Nanocrystal Bionanofilms. Issue 18 (15th January 2022) - Shakil, Ahmad; Kim, Sunghan; Polycarpou, Andreas A.
Abstract: Graphene oxide (GO), silk fibroin (SF), and cellulose nanocrystal (CNC) nanocomposite is a novel biomaterial with superior mechanical properties. Elevated temperature nanoindentation experiments using constant load hold method are performed to investigate temperature‐dependent mechanical and creep behavior of the GO–SF–CNC nanocomposite. Hardness and reduced modulus of GO–SF–CNC are determined from experiments at 25, 40, 60, 80, and 100 °C, and yield strength and creep coefficients are predicted from finite element analysis using two‐layer viscoplasticity theory. Results show that increasing the temperature from 25 to 80 °C, hardness, reduced modulus, and yield strength of GO–SF–CNC nanocomposite dramatically increase by 112%, 40%, and 140% respectively, and creep displacements during constant load hold reduce by 53%. It is attributed to increasing in crystallizations in the nanocomposite because of increasing in β‐sheet formations of SF material and reduction in water molecules in CNC material. However, at 100 °C, the mechanical properties deteriorate, and creep displacements increase because of water evaporation from the nanocomposite, making it weaker. Hardness‐to‐yield strength ratio is found within 1.84–2.06. Maximum creep exponent is 2.9 at 40 °C, which reduces to 2.06 at 80 °C and again increases to 2.27 at 100 °C. Abstract : Graphene oxide (GO), silk fibroin (SF), and cellulose nanocrystal (CNC) biofilms are prepared using spin‐assisted layer‐by‐layer assembly technique for precise control of very thin layered structures. Unique temperature‐dependent creep properties make the GO–SF–CNC film a potential bio‐nanomaterial for elevated temperature applications, such as flexible electronics and thermal interface materials.